Steep keratometry and central pachymetry after corneal collagen cross-linking procedure in patients with keratoconus - Resan, Mirko; Vukosavljević, Miroslav; Stanić, Elisaveta; Kovač, Bojan; Ristić, Dragana; Petrović, Maja; Pajić-Eggspuehler, Brigitte; Pajić, Bojan (Vojnosanitetski pregled, 2021)
Background/Aim. Keratoconus is a disorder of the eye which results in progressive thinning of the cornea. The cross-linking procedure (CXL) is applied in the treatment of initial progredient forms of keratoconus. It is aiming at increasing biomechanical stability of corneal stromal tissue to slow down or stop progressing the ectatic disorder. The aim of the study was to examine the effect of CXL procedure on values of steep keratometry (K2) and central pachymetry (CCT) six months after the intervention in keratoconusaffected patients. Methods. Clinical prospective cohort study included 30 eyes of 29 patients suffering from keratoconus. All patients were examined on Allegro-Oculyzer in order to diagnose and follow up keratoconus, thus obtaining corneal topography parameters and parameters important for this study: K2 and CCT, preoperatively and six months postoperatively. The CXL procedure was carried out by following the modified Dresden Protocol. Results. K2 mean value was 49.01 ± 3.99 diopter (Dpt) preoperatively and 48.06 ± 4.46 Dpt six months postoperatively. K2 decreased six months postoperatively by 0.95 Dpt, proportionally in all patients. Student’s paired sample t test showed that average decrease of K2 (d̄ = 0.95 Dpt) was highly statistically significant (t = 3.381; p < 0.01). CCT mean value was 480.17 ± 36.62 μm preoperatively and 444.37 ± 45.01 μm six months postoperatively. CCT decreased six months postoperatively by 35.8 μm, proportionally in all patients. Student’s paired sample t test showed that average decrease of CCT (d̄ = 35.8 μm) was highly statistically important (t = 6.40; p < 0.001)). Conclusion. Application of CXL procedure in the treatment of keratoconus with confirmed progression highly reduces steep keratometry and central pachymetry six months postoperatively. By steep keratometry reducing effect the CXL procedure is efficient in the treatment of keratoconus, especially its initial stages.